MMPDS-13 : Metallic materials properties development and standardization (MMPDS). Chapters 1-9. (Federal Aviation Administration ; Battelle Memorial Institute, 2018)
"MMPDS-13 supersedes MMPDS-12 and prior editions of the MMPDS handbook"--Page i